Humanising governance and management with spirituality - Mhd Sarif, Suhaimi; Ismail, Yusof (Routledge, Taylor & Francis Group, 2025)
This chapter advocates the incorporation of spirituality into the process of humanising government and management. This approach aims to fill the gap in current practices that lack a spiritually established framework for fulfilling human roles, functions, and responsibilities. Organisations should deliberately promote an environment that consistently treats individuals, both within and beyond their direct responsibility, with respect, dignity, and compassion. It is important for all stakeholders, each with their distinct requirements and viewpoints, to have a shared understanding of these values. An inclusive work environment that is imbued with these elements fosters a sense of worth, recognition, and empowerment among employees, enabling them to make their utmost contributions.